PEMBERDAYAAN PENENUN TEMBE NGGOLI DI KABUPATEN BIMA (STUDI KASUS DESA LEU KAB.BIMA) - Nurjulaifa Nurjulaifa; Wulandari Wulandari; Intisari Haryanti (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2022)
To make the community independent and develop the potentials possessed by the community, the community is not only the recipient of the results but must be actively involved and participate in development activities, so that independence is realized in the community. The traditional weaving of mbojo cloth is produced manually using traditional weaving tools, not machines. The type of research that will be used in this research is descriptive with a quantitative approach. A research method that describes the characteristics or phenomena of empowerment of tembe nggoli weavers in Bima Regency, especially for research involving research subjects from certain community groups, namely weavers in Leu Village, Bolo District, Bima Regency. Based on the results of the analysis and hypothesis testing, conclusions can be drawn in this study which states that there is empowerment of tembe nggoli weavers in Bima district.